3D modeling of discontinuities using GPR in a commercial size ornamental limestone block. (30th March 2018) - Elkarmoty, Mohamed; Tinti, Francesco; Kasmaeeyazdi, Sara; Bonduà, Stefano; Bruno, Roberto
Graphical abstract: Highlights: GPR allowed to detect discontinuities of tiny-size aperture in a limestone block. Discontinuities and defects were deterministically modeled and visualized in 3D. It's the first kind of this application in the commercial size scale of stone blocks. The authors will use the resulting model for the cutting optimization of slabs. Abstract: Discontinuities can be hidden or out-cropping with variable aperture sizes in rock media. Obtaining deterministic geo-spatial features of discontinuities inside quarried ornamental stone blocks is a decision-making tool for the post processing phase of cutting slabs. In a case study of a limestone block, discontinuities were detected by the Ground Penetrating Radar (GPR) through a high frequency antenna (700 MHz) and deterministically modeled in three dimensions following the method presented in Elkarmoty et al. (2017). The use of the 700 MHz GPR antenna in this kind of rock allowed to detect tiny-size apertures of discontinuities. The results showed that it is possible to detect and model not only the outcropping discontinuities, but also the hidden ones. Hidden three-dimensional voids or defects were detected and modeled as well. The resulting model was visualized in different orientations, using a 3D data visualization software package, for a better perception of the results.